PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA ASN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DINAS LINGKUNGAN HIDUP DI KABUPATEN SITUBONDO - Khoiriyah, Siti; Arief, Mohammad Yahya; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2023)
The Environmental Service is the executor of government affairs in the environmental sector, led by the Head of Service, who is domiciled under and accountable to the Regent through the Regional Secretary. The Environmental Service has the task of assisting the Regent in carrying out government affairs in the environmental sector. This research aims to analyze and test the effect of Leadership and Work discipline on Performance ASN at the Environmental Service through Job satisfaction. This research is explanatory. The population in this study is the State Civil Apparatus (ASN) at the Environmental Service. The sampling technique was determined by Probability sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that Leadership has a significant positive effect on Job satisfaction, Work discipline has a significant positive effect on Job satisfaction, Leadership has a negative but insignificant effect on State Civil Apparatus Performance, Work discipline has a positive but insignificant effect on State Civil Apparatus Performance, Job satisfaction has a positive but insignificant effect on State Civil Apparatus Performance. Hypothesis testing results Leadership does not significantly affect the performance of the State Civil Apparatus through job satisfaction; work discipline does not significantly affect the performance of the State Civil Apparatus through job satisfaction.